Short‐term ventriculo‐arterial coupling and myocardial work efficiency in preterm infants undergoing percutaneous patent ductus arteriosus closure. Issue 22 (21st November 2021) - Bischoff, Adrianne R.; Stanford, Amy H.; McNamara, Patrick J.
Abstract: Definitive closure of a patent ductus arteriosus (PDA) causes significant changes in loading conditions of the left ventricle (LV) which can lead to cardiorespiratory instability including hypotension, low cardiac output, oxygenation, and ventilation impairment. Physiological insights of the adaptation of the LV can be gained by looking at ventriculo‐arterial coupling (VAC) and myocardial work‐energetics. We conducted a retrospective cohort study of preterm infants with echocardiographic assessment of VAC parameters, including end‐systolic and arterial elastance (EES, EA ), and myocardial work indices derived from longitudinal strain analysis before and 1‐h after percutaneous PDA closure. A total of 35 patients were included with mean [±SD] age at intervention of 30.8 ± 9.9 days and median [IQR] weight of 1130 [995, 1318] grams. There was a reduction in preload and stroke volume, an increase in EA (38.6 ± 11.4 vs. 60 ± 15.1 mmHg/ml/kg, p  < 0.001) and in EES (72 [61.5, 109.8] vs. 91.6 [72.2, 125.2] mmHg/ml/kg, p  = 0.003) post‐closure. Myocardial work indices reduced after PDA closure, including global work efficiency (93.9 ± 2.3 vs. 91.1 ± 3.6%, p  < 0.001). A total of 17 (48.6%) patients developed post‐closure instability which was associated with younger age, lower preload, and higher EA and EES . Percutaneous PDA closure is associated with major short‐term changes in VAC and myocardium energetics, which may provide novel insights on the physiology of PDA closure and on the differential vulnerability to changes in loading conditions. Abstract : Definitive closure of patent ductus arteriosus is associated with significant changes in ventriculo‐arterial coupling and myocardial work indices including reduced preload, stroke volume, global longitudinal strain, and ventricular efficiency, with increased arterial elastance. Patients who develop cardiorespiratory instability after the procedure have higher arterial and end‐systolic elastance. These data may provide an enhanced understanding of the physiology of patent ductus arteriosus closure and serve as a guide to optimize care and provide targeted therapies in vulnerable preterm infants.